Muscle, Femininity, and Stigma: A Feminist Exploration of Women’s Bodybuilding - JUABAN, Janice; MOLNÁR, Győző; HAMAR, Pál; SOÓS, István (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Becoming a bodybuilder does not ‘naturally’ correspond to the social expectations traditionally directed towards women. The discipline demands extensive training and other lifestyle commitments in building a muscular female body. Drawing on personal experiences, this project explores key dimensions of a journey through the world of bodybuilding. Utilizing a feminist approach and the concept of stigma, the study focuses on the emotional and physical labour involved in developing a muscular physique while simultaneously navigating the socio-cultural expectations attached to femininity. This article centres on a three-year period and includes insights gained from a European competition’s Figure and Physique divisions. Central to this exploration is the tension between constructing a muscular body and negotiating the challenges of being a woman in the male-dominated subculture of bodybuilding. Article history: Received 2025 August 18; Revised 2025 September30; Accepted 2025 October 10;Available online 2025 November 20; Available print 2025 November 30